Development of a Problem-Solving Oriented Interactive E-Module as a Learning Media on the Topic of Biodiversity - Puluhulawa, Amelia Endang; Katili, Abubakar Sidik; Kyai Baderan, Dewi Wahyuni (Jurnal Pendidikan MIPA, 2022)
The purpose of the research is to obtain an interactive e-module learning media oriented to the problem-solving skills of biodiversity materials that are valid, practical, and effective. This type of research is 4D model development research (Define, Design, Develop, Disseminate). The results found that the validity test of the assessment of material expert validators, media experts, and teachers was sequentially scored (x) 95.10%, 85.83%, and 94.17% (very good). The practicality test for the implementation of learning in small groups and large group trials was scored (x) 94.12%, student activity was sequentially scored 85% and 87.62%, and student responses were sequentially scored 85% and 87.9% (all of these results belonged to the category of " very practical"). The effectiveness test of the N-Gain value in small group trials (0.64 "quite effective') and large groups (0.70 "effective"). In conclusion, the module developed is valid, practical, and effective in Biology learning process at SMA Negeri 2 Gorontalo.Keywords: e-module, problem-solving skill, research and development.DOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp207-221